Peningkatan Hasil Belajar IPAS Materi Daerahku Kebanggaanku dengan Media Kuis Interaktif Di Kelas V SD - Agustiningrum, Indah Auliya; Dewi, Nurul Kusuma; Ayuningtiyas, Dita Mayang (Jurnal Likhitaprajna, 2024)
This Classroom Action Research aims to improve the learning outcomes of fifth-grade students in Science (IPAS) by implementing Problem-Based Learning (PBL) supported by interactive quizzes. The study was conducted at an elementary school involving 26 students over two cycles, encompassing planning, action, observation, and reflection stages. Data were collected through tests, observations, and interviews. The results indicate that PBL with interactive quizzes significantly enhances student engagement and understanding, as evidenced by the increase in test scores and positive feedback. The percentage of learning outcomes improved from 57.7% in the pre-cycle to 69.2% in Cycle I, and reached 92.3% in Cycle II. Observations and interviews also showed that students felt more interested, motivated, and better understood the material through this method. Thus, the use of interactive quizzes in PBL has proven effective in enhancing student learning outcomes.